Don't send flowers - Solares, Martín, 1970- (Black Cat, an imprint of Grove Atlantic, 2018)
From a writer whose work has been praised by Junot Díaz as "Latin American fiction at its pulpy phantasmagorical finest," Don't Send Flowers is a riveting novel centered on Carlos Treviño, a retired police detective in northern Mexico who has to go up against the corruption and widespread violence that caused him to leave the force, when he's hired by a wealthy businessman to find his missing daughter.